A Bibliography of Torres Strait Education - Shnukal, Anna (The Australian Journal of Indigenous Education, 2003)
Abstract This non-selective bibliography is limited to published material and is part of the Bibliography of Torres Strait to be found on the Aboriginal andTorres Strait Islander Studies Unit’s website at . Torres Strait Islander authors are marked with an asterisk.